2017
DOI: 10.1016/j.cardfail.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased Left Ventricular Diastolic Stiffness Is Associated With Heart Failure Symptoms in Aortic Stenosis Patients With Preserved Ejection Fraction

Abstract: Background Clinical risk factors associated with heart failure (HF) symptoms in aortic stenosis (AS) patients with preserved ejection fraction (EF) have not been fully identified. We hypothesized that left ventricular (LV) diastolic stiffness is associated with HF symptoms in patients with AS. Methods and Results We retrospectively evaluated 275 patients with at least moderate AS (aortic valve area <1.5 cm2) and preserved EF (≥50%). LV diastolic stiffness was evaluated with the use of echocardiographic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…LV diastolic dysfunction, and subsequently indices of LV myocardial and chamber stiffness had been associated with symptomatic AS, especially dyspnea 30 . These findings had suggested that heart failure symptoms in severe AS were driven by high LV filling pressures consequent to LV hypertrophy and diastolic dysfunction 31 . The actual relationship between LV remodeling and diastolic filling however is highly complex, where both early relaxation and passive LV filling later in diastole have demonstrated important roles in the development of heart failure symptoms 32 .…”
Section: Discussionmentioning
confidence: 99%
“…LV diastolic dysfunction, and subsequently indices of LV myocardial and chamber stiffness had been associated with symptomatic AS, especially dyspnea 30 . These findings had suggested that heart failure symptoms in severe AS were driven by high LV filling pressures consequent to LV hypertrophy and diastolic dysfunction 31 . The actual relationship between LV remodeling and diastolic filling however is highly complex, where both early relaxation and passive LV filling later in diastole have demonstrated important roles in the development of heart failure symptoms 32 .…”
Section: Discussionmentioning
confidence: 99%
“…0.33 had a higher rate of death or HF hospitalization than those with DWS > 0.33, even after adjustment for age, sex, log B-type natriuretic peptide, LV geometry and log E/e'. Similarly, Kamimura D et al (49) in 2017 found DWS to be significantly associated with HF symptoms in patients with AS with preserved ejection fraction (OR: 0.91, CI:0.86-0.96, P<0.005). Immediately thereafter, in 2018,Kamimura D et al (50) found both continuous and categorical DWS were independently associated with incident HF after adjustment for traditional risk factors and incident coronary artery disease (HR 1.21, 95%CI 1.04-1.41 for 0.1 decrease in continuous DWS, P= 0.014; HR 1.40, 95%CI 1.05-1.87 for the smallest DWS quintile vs other combined quintiles, P = 0.022), and in 2019 a study by Tsujimoto S, et al (51) showed low DWS ([?]…”
Section: The Epicardial Movement Index (Emi) and Diastolic Wall Strai...mentioning
confidence: 81%
“…Many studies attempted to identify echocardiographic parameters that would predict outcome of LG SAS with preserved LVEF. AVAi, pressure gradients, dobutamine testing and other parameters have been analyzed, but the results were not always consistent [ 26 30 ]. The current study also showed that the traditional echocardiographic measures for the severity of AS (AVAi and pressure gradients) were not significant in predicting all-cause mortality in LG SAS with preserved LVEF.…”
Section: Discussionmentioning
confidence: 99%